Predicting Revalidation Examination Performance of Radiologic Technology Students: A Structural Equation Modelling Approach - Ampaso, Abdul; Abedin, Sittiehaya; Batalo, Jahara; Ampaso, Rowena; Abdullah, Habab; Amer, Nadhra (Future Science / FSH-PH Publications, 2022)
One of today’s major problems in higher education system is the academic failure of medical science students with apparent yearly reports of experiencing probation, insufficient medical knowledge, increase educational semester, and drop out incidences. This study aims to predict the revalidation examination score of the Radiologic Technology interns of a higher education institution in Iligan City. An exploratory research with descriptive correlation design was used to investigate the interrelationship between the predicting variables in this study. The researchers adopted the Grit-S Scale structured questionnaire that was developed by Duckworth and Quinn (2009), which was designed to measure the grit level of respondents. This tool was used to elicit the needed primary data on the currently enrolled 26 radiologic technology interns at a higher institution in Iligan City. The survey was administered online via Google form. The secondary data, which constitutes of monthly examination score, case study scores, and revalidation examination was solicited in the CRT Program Head. Census sampling was employed in this research to obtain a more satisfactory response. The study showed that the indicators in monthly examination obtained a total mean of 31.64 with an SD of 14.35. These low scores were manifested in their performance in revalidation examination, which revealed a total mean score of 52.73 with a ± 16.02 SD. On the contrary, the respondents obtained high scores in case study with overall mean score of 95.42 and an SD of ± 2.83. The overall grit level of the respondents demonstrated a moderate description. Furthermore, the findings of this study also revealed that there is a significant relationship between monthly examination and revalidation examination. The strength of correlation is direct and strong as revealed by the coefficient of 0.904. Meanwhile, there is no significant relationship between revalidation examination score and case study score (p=0.537); between revalidation examination score and grit level (p=0.833); between grit level and monthly examination score (p=0.831) and between grit level and case study score (p=0.071). The positive influence of monthly examination implies that respondents who scored high in the monthly examination would be predicted to score high also in the revalidation examination. These findings can help the faculty and program head in drafting policies and the improvement of academic and clinical performance of students in revalidation exam.